2017
DOI: 10.1038/s41551-017-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

A cryptography-based approach for movement decoding

Abstract: Brain decoders use neural recordings to infer a user's activity or intent. To train a decoder, we generally need infer the variables of interest (covariates) using simultaneously measured neural activity. However, there are many cases where this approach is not possible. Here we overcome this problem by introducing a fundamentally new approach for decoding called distribution alignment decoding (DAD). We use the statistics of movement, much like cryptographers use the statistics of language, to find a mapping … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…For instance, the map into the latent manifold could be nonlinear, e.g. using Isomap [7,41]. There also exist several nonlinear alignment procedures, such as kernel CCA or Distance Covariance Analysis , although such extensions have yet to translate into BCI practice [42].…”
Section: Across-animal Decoding In the Rodent Olfactory Bulbmentioning
confidence: 99%
“…For instance, the map into the latent manifold could be nonlinear, e.g. using Isomap [7,41]. There also exist several nonlinear alignment procedures, such as kernel CCA or Distance Covariance Analysis , although such extensions have yet to translate into BCI practice [42].…”
Section: Across-animal Decoding In the Rodent Olfactory Bulbmentioning
confidence: 99%
“…The stable latent dynamics reported here offer an intriguing alternative to existing approaches: BCIs based on latent dynamics as opposed to recorded neural activity could be periodically aligned through a linear procedure such as CCA, thereby achieving stable performance through months or even years of neural turnover. Recent work has shown that approaches based on latent dynamics can be used to improve decoding stability 70,71,38 , adjust for changes in neural inputs 72 , and enable unsupervised decoding 68 .…”
Section: Practical Implications For Braincomputer Interfacesmentioning
confidence: 99%
“…Due to neural turnover, the neural signals that provide inputs to these decoders typically change after a few days, rapidly leading to degraded BCI performance 65,66 . Many groups have been working to develop computational techniques to continually recalibrate these decoders, and thereby restore some of their degraded function 67,68 . Other groups have suggested that the use of input signals such as multiunit threshold crossings 65 or local field potentials 69 could reduce the magnitude of these changes, at the risk of reducing the amount of available information.…”
Section: Practical Implications For Braincomputer Interfacesmentioning
confidence: 99%
“…In addition, we could interpret the improvement in the decoding performance gained with the encoding model from the perspective of statistics of movements. Kording, et al 42 proposed a fundamentally new approach, alignment decoding (DAD), leveraging the statistics of movements. The understanding of the statistics of movements can help us in many situations where obtaining simultaneous recordings of both neural activity and kinematics is challenging, expensive, or impossible.…”
Section: Discussionmentioning
confidence: 99%